Attendance Management System an Android Application - Bhattacharjee, Saptorshi; Kundu, Dipankar; Raychaudhuri, Shinjini; Chakraborty, Papiya (International Journal of Computer Sciences and Engineering, 2025)
In the last few years due to improvement of technology education system in India has developed. Smart Class, video conferencing is some of the examples of modern trends in educational system. Student Attendance Management Systemis an android based application which helps the institute to move forward, fulfill their vision accomplish their goals.It generates the attendance of the student on basis of their presence in class. It is maintained on the daily basis of their attendance. The staffs will be provided with the separate username &password to take the student’s status. It helps the teacher to take attendance through their smart phone and to keep the record of the attendance in their pocket for any time use.